The Perception of University Students and Workers on Foodservice offered by the University’s Cafeteria - Bourne, Paul Andrew (Journal of Advanced Research in English & Education, 2021)
Universities’ food services are one of the largest sectors of the foodservice industry, and studies have shown that this market is a growing one, especially at universities. It has a goal to satisfy the people’s basic need for food as well as their minds’ appetite and nutritional/health knowledge. The study was conducted to evaluate the customer experience at the cafeteria, determining the nutritional challenges of customers and the diverse needs of its customers. People’s perception of a good quality cafeteria was also studied, and it was also aimed to share the empirical findings with the policymakers and implement them to create the ambiance and experience that are in demand by the students and workers of the institution. A descriptive survey was conducted at the cafeteria to collect data that would answer the aforementioned objectives. This study utilized a descriptive research design (cross-sectional standardized survey). The data collectors visited the cafeteria at different times, like from opening to closing hours or at certain intervals during the day. One thousand instruments were printed, between January–May 2018, 600 respondents were contacted, and 488 returned the standardized questionnaire among those. When the respondents were asked ‘Where do you normally get lunch on school days?’ the majority of the sampled respondents indicated that normally they consume food off the campus (47.3%) as compared to 37.1% who do so at the institution’s Cafeteria. Most of the respondents indicated that they eat at the Cafeteria 3–4 times a week compared to only 20.5%. The majority of the those who eat at the Cafeteria for the 5 months consumed sandwiches and wraps (30.9%) followed by deserts (24.2%), fruits (22.4%), main meal (12.6%), soups (8.7%) and lastly salads (1.1%). Respondents’ views on rating of the health content of the food are presented in a bar graph. The Cafeteria is a social agent that enhances students’ perception of him/her as well as the place of interaction. Therefore, peoples’ satisfaction with food is a factor in the discourse of human existence, and this means that food quality is a part of the general dialogue of university students’ satisfaction with the product offerings of the institution. How to cite this article:  Bourne PA. The Perception of University Students and Workers on Foodservice offered by the University’s Cafeteria. J Adv Res Eng & Edu 2020; 5(1): 39-52.